Adapting Solar Cells With Polysilicon Passivated Contacts to Radiation-Rich Environments - Nicolas Enjalbert; Romain Cariou; Sébastien Dubois (SiliconPV Conference Proceedings)
In the context of increased space photovoltaic power needs and cost reduction pressures, silicon solar cells spark a new interest for space missions. This is even truer if the cost-effective mass-produced silicon technologies can be adapted to the specific constraints of the space environment. This study successfully demonstrated that cells with polycrystalline silicon-based passivated contacts could be adapted to the main prerequisites for space missions. Indeed, flexible and lightweight alternative polysilicon passivated contacts cells were prepared from gallium-doped substrates, with post-irradiation performances as good as those of conventional (thicker) PERC devices. The influence of the doping level was investigated. Low doping levels mitigate the radiation-induced degradation of the bulk carrier lifetime and therefore of the short-circuit current density, but result in lower open circuit voltages. Furthermore, it was shown that the surface and bulk hydrogenation step investigated in this study does not influence the post-irradiation effective carrier lifetime and its evolution under prolonged illumination in the temperature range 80°C-100°C (at least for the durations investigated here).